Synthesis, radiolabeling, and in vitro and in vivo characterization of heterobivalent peptidic agents for bispecific EGFR and integrin αvβ3 targeting - Braun, Diana; Judmann, Benedikt; Cheng, Xia; Wängler, Björn; Schirrmacher, Ralf; Fricker, Gert; Wängler, Carmen (ACS omega, 2023)
Radiolabeled heterobivalent peptidic ligands (HBPLs) are a highly promising compound class for the sensitive and specific visualization of tumors as they often exhibit superior properties compared to their monospecific counterparts and are able to concomitantly or complementarily address different receptor types. The combination of two receptor-specific agents targeting the epidermal growth factor receptor (EGFR) and the integrin αvβ3 in one HBPL would constitute a synergistic combination of binding motifs as these two receptor types are concurrently overexpressed on several human tumor types and are closely associated with disease progression and metastasis. Here, we designed and synthesized two heterobivalent radioligands consisting of the EGFR-specific peptide GE11 and αvβ3-specific cyclic RGD peptides, bearing a (1,4,7-triazacyclononane-4,7-diyl)diacetic acid-1-glutaric acid chelator for efficient radiolabeling and linkers of different lengths between both peptides. Both HBPLs were radiolabeled with 68Ga3+ in high radiochemical yields, purities of 96-99%, and molar activities of 36-88 GBq/μmol. [68Ga]Ga-1 and [68Ga]Ga-2 were evaluated for their logD(7.4) and stability toward degradation by human serum peptidases, showing a high hydrophilicity for both agents of −3.07 ± 0.01 and −3.44 ± 0.08 as well as a high stability toward peptidase degradation in human serum with half-lives of 272 and 237 min, respectively. Further on, the in vitro receptor binding profiles of both HBPLs to the target EGF and integrin αvβ3 receptors were assessed on EGFR-positive A431 and αvβ3-positive U87MG cells. Finally, we investigated the in vivo pharmacokinetics of HBPL [68Ga]Ga-1 by positron emission tomography/computed tomography imaging in A431 tumor-bearing xenograft mice to assess its potential for the receptor-specific visualization of EGFR- and/or αvβ3-expressing tumors. In these experiments, [68Ga]Ga-1 demonstrated a tumor uptake of 2.79 ± 1.66% ID/g, being higher than in all other organs and tissues apart from kidneys and blood at 2 h p.i. Receptor blocking studies revealed the observed tumor uptake to be solely mediated by integrin αvβ3, whereas no contribution of the GE11 peptide sequence to tumor uptake via the EGFR could be determined. Thus, the approach to develop radiolabeled EGFR- and integrin αvβ3-bispecific HBPLs is in general feasible although another peptide lead structure than GE11 should be used as the basis for the EGFR-specific part of the agents.
Im Titel sind der Buchstabe "v" und die Ziffer "3" tiefgestellt
Online veröffentlicht: 4. January 2023
Gesehen am 15.10.2024